Investigation of Radio Frequency Signal Propagation of Wireless Services in Oyo, Oyo State, South Western Nigeria - Sheu, Akeem Lawal; Suleman, K. O.; Adeniji, Q. A.; Azeez, I. A. (Iraqi Journal of Physics, 2022)
This study reported the investigation of the Radio Frequency (RF) signal propagation of Global System for Mobile Communications (GSM) coverage in Emmanuel Alayande College of Education (EACOED), Oyo, Oyo State, Nigeria. The study aims at amplifying the quality of service and augment end users’ sensitivity of the wireless services operation. The drive test method is adopted with estimation of coverage level and received signal strength. The Network Cell Info Lite application installed in three INFINIX GSM mobile phones was employed to take the measurement of the signal strength received from the transmitting stations of different mobile networks. The results of the study revealed that MTN has the maximum signal strength with a mean value of - 68.33 dBm, directly followed by Globacom (-80.41 dBm) and Airtel with -83.13 dBm. The Airtel signal has a conspicuously invariable poor performance with coverage level of 41.66 %. Conversely, the MTN and Globacom signal reception are observed to surpass the Airtel network within the college premises with 83.33 % and 60.41 % coverage level respectively. This implies that the signal quality for MTN and Globacom networks were comparatively disseminated within the college with inconsequential fluctuations in quality while Airtel signal is subsided and weaken. The poor performance in some areas was due to the presence of physical impediments and far distances location of base station antennas in the promulgation locations. This study therefore suggested that Airtel and Globacom Base Transceiver Stations (BTS) should be positioned within the college to improve good network reportage level.